Cultivating emerging leadership competencies for individual and organizational success - Tong Wooi Chow; Harwindar Singh (Annals of Management and Organization Research, 2022)
Purpose: Leadership is a critical factor for individual and organizational success in today's complex and dynamic business environments. Effective leaders possess a wide range of competencies that enable them to inspire, guide, and influence others to achieve common goals. This study examines the concept of leadership competencies and their roles in fostering individual and organizational success. Research methodology: This methodological approach is based on a review of published literature outlining the significance of the leadership competency concept and the four key emerging leadership competencies for organizational performance. Results: The findings indicate the importance of the competency paradigm, which contributes to the quality of leadership. Specifically, key emerging competencies will provide valuable insights for leaders, human resource professionals, and researchers in the field of leadership development. Limitations: The research review method is based on secondary data; hence, it has its limitations. Owing to the evolving dynamic contextual leadership landscape, some crucial leadership competencies may emerge over time in some geographical organizational contexts. This necessitates a continual study and analysis of the evolving trends in emerging leadership competencies in organizations. Contribution: This study contributes to enhancing insights and knowledge of leadership development. Other concepts discussed include the competency definitions, competency model, skill-based model, and integrative competency framework. Novelty: The research and discussion on the proposed integrative emerging leadership competencies add to the merit of this paper. There is evidence that the competency framework results in individual and organizational performance.